Implementation of Regulatory Policy on the Control of Shadow Terminals as an Effort to Improve Transport Services in Palopo City - Ilyas, Ilyas; Qadar, Jamal; Ikram, Ikram (International Journal of Business, Law, and Education, 2024)
This research aims to analyse the implementation of regulatory policies towards the control of shadow terminals as an effort to improve transportation services in Palopo City. The type of research is descriptive qualitative. The subjects of this research are the apparatus of the Transportation Department of Palopo City as the regulator and implementer of regulatory policies, as well as individuals or communities who are observers of transportation, public transport operators and users of public transport services. Informants consisted of 4 officials and 3 people from the community. Data collection techniques were observation, interview and documentation study. Qualitative data analysis technique. The results of the research on the implementation of regulatory policies on the control of shadow terminals as an effort to improve transport services in Palopo City in general both from the perspective of the apparatus and the community have not run optimally. Supporting factors based on informants' assessment include: (1) policy formulation, (2) attitude and commitment of the apparatus and (3) availability of SOPs. The inhibiting factors according to the informants include: (1) weak enforcement of regulations, (2) inadequate human resources, (3) policy products have not been implemented periodically, (4) not optimal coordination between stakeholders, (5) the behaviour of people using shadow terminals.